APPLICATION OF COOPERATIVE LEARNING TYPE EXAMPLES NON EXAMPLES TOWARDS STUDENTS LEARNING ACTIVITIES AND LEARNING OUTCOMES IN ENVIRONMENTAL POLLUTION SUBJECT MATTER - Yudi Trisila; Tri Jalmo Tri Jalmo; Pramudiyanti Pramudiyanti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Based on observation and interview with biology teacher in SMA N 1 Ambarawa, students learning activities and outcomes were not optimally developed yet. An alternative that can be used to improve learning activities and outcomes is using applicating cooperative learning model type examples non examples.This experiment aims to find out the influence of applicating cooperative learning model type examples non examples towards improvement of students learning activities and outcomes.This study is quasi experiment using pretest posttest group non equivalent design. Sample in this experiment are students from X.1 and X.2  which obtained from population by cluster random sampling method. Quantitative data is outcomes that obtained from average of pretest and posttest scores which statistically analyzed with U-test using SPSS version 16 in 95% confidence levels. Qualitative data are student’s learning activities and students responses about applicating cooperative learning model type examples non examples which descriptively analyzed. Result of this study shown that the average of students outcomes in experimental class are higher than control (experiment= 72.3; control = 58.0). The average of student learning activities percentage in all observed aspects in experimental class shown higher enhancement than control (experiment = 90.8; control = 60.25). The students also gives positive responses to applicating cooperative learning model type examples non examples  Keywords: Cooperative learning type examples non examples, learning activities, outcomes.